Etiological Evaluation of Congenital Hypothyroidism Cases - Ayşe Anık; İlkay Bahar Balaban Berber; Tolga Ünüvar; Ahmet Anık (Galenos Publishing House, 2020)
INTRODUCTION: The aim of this study was to determine, (i) the cause of congenital hypothyroidism (permanent or transient), (ii) the etiological cause of persistent congenital hypothyroidism and (iii) to investigate the role of clinical and laboratory data in predicting persistent and transient congenital hypothyroidism. METHODS: Patients with congenital hypothyroidism who were started L-thyroxine treatment and discontinued at the age of 3 years were included in the study. The data of the cases were obtained retrospectively from the hospital records. Serum thyroid hormones were measured of the cases 4 weeks after discontinuation of treatment at the age of 3 years. Patients with TSH> 10 mIU/mL were accepted as permanent hypothyroidism and those with normal TSH value for 6 months were accepted as transient hypothyroidism. RESULTS: A total of 63 patients were included in the study. Permanent congenital hypothyroidism was detected in 16 (25%: 9 females, and 7 males) and transient congenital hypothyroidism in 47 (75%: 22 females, and 25 males) cases. There was no difference between the permanent and transient groups in terms of gender, gestational week, birth weight, age at diagnosis, physical examination findings at the time of diagnosis, serum fT4, TSH levels, and initial L-thyroxine doses. While thyroid ultrasonography was normal in all patients in the transient hypothyroidism group, dysgenesis was detected in 9 (56%), and dyshormonogenesis in 1 (6%) patient. The mean thyroxin dose in permanent congenital hypothyroidism group was significantly higher than the transient group at the time of treatment cessation (2.8+-0.9 and 1.2+-0.5 mcg/kg/day, p<0.001, respectively). L-thyroxin dose of >2.1 mcg/kg/d was 81% sensitive and 90% specific for predicting permanent congenital hypothyroidism (p<0.001). DISCUSSION AND CONCLUSION: It has been shown that the most common etiologic cause of congenital hypothyroidism is transient hypothyroidism. Thyroxine dose at the time of treatment cessation was found to be the most important determinant in the differentiation of permanent and transient congenital hypothyroidism.